In vitro kinetic study of donepezil N- oxide metabolites - Faris T. Abachi; Ammar B. Behnan; Riyath A. Atto (University of Mosul, 2011)
Objective: The aim of this study was to examine the metabolism of donepezil via N - oxidation of donepezil HCl in vitro, and the kinetic studies at a temperature similar to that of the human body. Methods: Direct reaction of donepezil with hydrogen peroxide and formic acid at room temperature, the N - oxide undergoes a series of rearrangements, the reaction was followed by ultraviolet at λmax= 268 nm at 37 °C. The donepezil N- oxide was also tested as potential cholinesterase inhibitor using electrometric for cholinesterase determination. Results: According to the present work , the structure of donepzil N- oxide was elucidated using spectroscopic analysis , also , in vitro kinetic study at 37 °C using ultraviolet spectrophotometer at λmax = 268 nm showed that the reaction proceeded at a first order reaction . Biologically, the compound was found to inhibit both plasma and erythrocyte cholinesterase activities in vitro .. Conclusion: We concluded that the N- oxide of denepezil undergoes a series of rearrangements, the reaction followed first order at 37 °C. It has a potential anticholinesterase activity